CRIMINAL LIABILITY FOR PROVOCATIVE ACTS COMMITTED BY DEMONSTRATORS DURING DEMONSTRATIONS - Muhammad Fadhlan Al Hafizh; Yuliana Yuli Wahyuningsih (RADJA PUBLIKA, 2025)
This study analyzes criminal liability for provocative acts committed by demonstrators during demonstrations and also explains the obstacles to law enforcement according to positive law in Indonesia. Freedom of speech guaranteed by the 1945 Constitution is strongly related to demonstrations because people are given the freedom to express their opinions in public with rules that must be implemented. However, in reality, in the field, there are still many provocative acts carried out by demonstrators that cause riots during demonstrations. This research method uses normative juridical with a statutory approach by examining the Criminal Code, Law No. 9 of 1998, the Security Law, Perkapolri 7/2012, and other laws relevant to the research conducted. The results of this study indicate that perpetrators of provocation can be subject to criminal liability under Articles 160, 170, and 212 –214 of the Criminal Code, depending on the form of the act and the consequences.